The Effect of the Parents' Education Background and Income on the English Study Achievement of the Eighth Grade Students at SMP HKBP Sidorame - Hagai Depsin Sembiring; Rupa Shema; Christina Natalina Saragi (Sean Institute, 2022)
Parental education levels are high must have high ideals of education of their children. While the income level of parents can assist students in meeting the needs of their schools so that students can undergo a process of education to the maximum. The writer wanted to know the high and low education The study population was students in class VIII SMP HKBP Sidorame 2022/2023 School Year spread as many as 100 students in forth classes. This research is 50 students as sample from classes A and B. There are three variables that were examined in this study, namely: the level of parental education (X1), income level of parents (X2) and student English achievement (Y). The collection of data retrieved through a questionnaire and documentation. Test Instrument made by the validity and reliability. Analysis of data using the percentage of regression analysis. Based on the calculation of the t-test for the parental education variable, it was obtained that it was 2,005 because t was stated with a positive sign, the higher the education of parents, the higher the English achievement of students. The results of the t-test calculation for the parent's income variable, it is obtained that t is 4.556 because t is indicated by a positive sign, the higher the income of parents, the higher the student's English achievement. Based on the results of research can be concluded that the study is partially or simultaneously. The results of that study suggested to the students to always be the spirit in the education process to achieve maximum learning achievement, as well as to parents to help encourage and meet the educational needs of students while in a state of low education and low income levels.